Green innovation performance: a multi-level analysis in the hotel sector. Issue 8 (23rd May 2022) - Bani-Melhem, Shaker; Al-Hawari, Mohd Ahmad; Mohd. Shamsudin, Faridahwati
Abstract: This multi-level study builds on the natural resource-based view and value-belief-norm theory to assess the effect of environmental innovation strategies on customer loyalty through the mediator of green innovation performance. It also examines whether leadership support for green innovation further strengthens the impact of such a strategy on green innovation performance and whether the effect of innovation performance further enhances loyalty among customers with environmental values. We collected multi-level data from multiple sources in 52 five-star chain-affiliated hotels in Dubai, surveying 39 operation managers, 39 human resource (HR) managers, 40 marketing managers, and 230 hotel guests/customers. Structural equation modelling was used to analyze the data. We found empirical support for all hypotheses. Specifically, we demonstrate that environmental strategy enhances customer loyalty through green innovation performance when there is strong leadership support for green innovation. We also show that customers who subscribe to environmental values are more likely to be loyal to green hotel organizations. Our study further outlines how hotel managers can use innovative green strategies to enhance customer loyalty, showing how our findings can shape management practices and future research.